Diversity management in organizations: a brief bibliographic review (Research, Society and Development, 2022)
Many organizations today use the concept of diversity management as a strategic differentiator to make them more competitive in the highly competitive market. Collaborators with diversified characteristics in the cultural, ethnic, gender spheres, among others, in contrast to the historical pattern of hiring of organizations, have gained presence in Brazilian companies. Thus, the main objective of this work is to carry out a narrative review about how diversity is managed in organizations in Brazil and how this theme can contribute both to a change in the issue of respect for differences in the work environment and to generate improvement in the performance of organizations The research was developed by means of a bibliographical analysis on some works developed on the management of diversity in companies. As main conclusions we have that there have been advances in the implementation of diversity management programs in the companies analyzed but, however, the implemented actions are still incipient, demanding more studies for a better development of the subject in the organizations. In case of diversity as an administrative practice, we see that the research is insufficient in the companies. Regarding the management of diversity related to the issue of race and people with disabilities. I see that there is still a small participation of professionals in the work environment and in leadership positions, demanding more inclusion programs. In relation to social inequality, educational exclusion and organizational learning, it has been verified, however, that inequality continues to be present. In relation to gender discrimination, despite the increase in female participation, inequalities have been greatly reduced.